Vitellointestinal Duct Anomalies in Infancy - Kadian, Yogender Singh; Verma, Anjali; Rattan, Kamal Nain; Kajal, Pardeep (Journal of Neonatal Surgery, 2016)
Background: Vitellointestinal duct (VID) or omphalomesenteric duct anomalies are secondary to the persistence of the embryonic vitelline duct, which normally obliterates by weeks 5–9 of intrauterine life. Methods: This is a retrospective analysis of a total of 16 patients of symptomatic remnants of vitellointestinal duct from period of Jan 2009 to May 2013. Results: Male to female ratio (M:F) was 4.3:1 and mean age of presentation was 2 months and their mode of presentation was: patent VID in 9 (56.25%) patients, umbilical cyst in 2(12.25%), umbilical granuloma in 2 (12.25%), and Meckel diverticulum as content of hernia sac in obstructed umbilical hernia in 1 (6.25%) patient. Two patients with umbilical fistula had severe electrolyte disturbance and died without surgical intervention. Conclusion: Persistent VID may have varied presentations in infancy. High output umbilical fistula and excessive bowel prolapse demand urgent surgical intervention to avoid morbidity and mortality.